Efficient catalytic production of levulinic acid over hydrothermally stable propyl sulfonic acid functionalized SBA-15 in γ-valerolactone-water system. Issue 4 (August 2021) - Cheng, Xi; Feng, Qingge; Ma, Dachao; Chen, Hongcheng; Zeng, Xu; Xing, Feifan; Teng, Jiayang
Abstract: To eco-friendly catalyze glucose to levulinic acid, recyclable acid catalyst has been researched. The synthesis process of propyl sulfonic acid functionalized SBA-15 was improved and the hydrophobic treatment was performed. The structure and functional groups of materials were characterized by X-ray diffraction, transmission electron microscopy, N2 adsorption–desorption isotherms, elemental analysis, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy and simultaneous thermal analysis. The catalytic activity, recyclability and hydrothermal stability of CH3 -SBA-15-SO3 H material were researched. The highest yield of levulinic acid at 61.56% was obtained at 180 ℃ for 2.5 h in γ-GVL-water solvent system, and the yield of levulinic acid was only decreased by 2% after 4 times reuse. The high degree of silicon polycondension and hydrophobic surface of CH3 -SBA-15-SO3 H were the key to maintain the hydrothermal stability. The CH3 -SBA-15-SO3 H solid acid had great potential in development and utilization of biomass resources. Graphical Abstract: Insights into the synthesis and properties of propyl sulfonic acid functionalized SBA-15 based on conversion of glucose to levulinic acid. ga1 Highlights: The CH3 -SBA-15-SO3 H sample aged at 180 ℃ had the best hydrothermal stability. CH3 -SBA-15-SO3 H sample exhibited excellent catalytic activity in γ-GVL-water system. Catalyst CH3 -SBA-15-SO3 H could be reused at least for 4 times.